Periprosthetic fracture around a loose hip or knee arthroplasty. Issue 1 (January 2016) - Sassoon, Adam; Haidukewych, George
Abstract : The number of people having total hip or knee replacement is growing at a steady rate; additionally total joint arthroplasty is being performed more frequently in younger patients with higher demands than has been previously observed. These factors working in concert generate an increased risk of periprosthetic fractures. The growing incidence of these injuries creates an impetus for orthopaedic surgeons to be more comfortable with their treatment. Periprosthetic fractures around loose hip or knee arthroplasty components represent a unique and challenging clinical problem, requiring a skill set drawing from advanced techniques in orthopaedic traumatology and revision arthroplasty. This review outlines the principles in tackling these difficult cases including fracture reduction maneuvers, provisional fixation, revision instrumentation, implant choices, and supplemental fixation around revision components. The primary objective of this study was to supply practical tips and tricks to supplement the knowledge of orthopaedic traumatologists and adult reconstruction surgeons so that they are able to effectively treat these complex injuries successfully.